Distinct acute stressors produce different intensity of anxiety-like behavior and differential glutamate release in zebrafish brain - Martins, Milena Letícia; Pinheiro, Emerson Feio; Saito, Geovanna Ayami; Lima, Caroline Araújo Costa De; Leão, Luana Ketlen Reis; Batista, Evander de Jesus Oliveira; Passos, Adelaide da Conceição Fonseca; Gouveia, Amauri; Oliveira, Karen Renata Herculano Matos; Herculano, Anderson Manoel (Frontiers in Behavioral Neuroscience, 2024)
Anxiety disorder is one of the most well-characterized behavioral disorders in individuals subjected to acute or chronic stress. However, few studies have demonstrated how different types of stressors can modulate the neurochemical alterations involved in the generation of anxiety. In this study, we hypothesize that subjects exposed to different aversive stimuli (mechanical, chemical, and spatial restriction) present varied intensities of anxiety-like responses associated with distinct patterns of gamma-aminobutyric acid (GABA) and glutamate release in the brain. Adult zebrafish, Danio rerio (n = 60), were randomly divided into four experimental groups; control, acute restraint stress (ARS), conspecific alarm substance (CAS), and chasing with net (CN). After the stress protocols, the animals were individually transferred to a novel tank diving test for behavioral analysis. Subsequently, their brains were collected and subjected to GABA and glutamate release assay for quantification by HPLC. Our behavioral results showed that all aversive stimuli were capable of inducing anxiety-like behavior. However, the impact of anxiogenic behavior was more prominent in the CN and CAS groups when compared to ARS. This phenomenon was evident in all analyzed behavioral parameters (time on top, freezing, mean speed, maximum speed, and erratic swimming). Our data also showed that all aversive stimuli significantly decreased GABA release compared to the control group. Only animals exposed to CN and CAS presented an increase in extracellular glutamate levels. Different acute stressors induced different levels of anxiety-like behavior in zebrafish as well as specific alterations in GABAergic and glutamatergic release in the brain. These results demonstrate the complexity of anxiety disorders, highlighting that both behavioral and neurochemical responses are highly context-dependent.